2018
DOI: 10.1002/ijc.31373
|View full text |Cite
|
Sign up to set email alerts
|

Associations between statin use and risk of non‐Hodgkin lymphomas by subtype

Abstract: Non-Hodgkin lymphomas (NHL) are a group of cancers with highly heterogeneous biology and clinical features. Statins are increasingly prescribed to prevent cardiovascular diseases. Early evidence shows a preventive effect of statins for some cancers, but their effect on NHL risk is unclear. We conducted a population-based nested case-control study involving 5,541 NHL cases and 27,315 controls matched for gender, age, place of residence and length of period of available prescription drug data. We assessed the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…They were further limited by reliance on questionnaires for measuring statin use; by lack of information about dose, duration and timing of use; and by grouping all statins regardless of their chemical or pharmacokinetic properties. We recently studied the effects of statins, as a class, on the incidence of several NHL subtypes, including CLL, and estimated an odds ratio (OR) of 0.89 [95% confidence interval (CI), 0.77-1.04) for CLL (18). In this article, we report on the association between CLL and use of several commonly used statins with different chemical structures, pharmacodynamics, and lipid-lowering effects.…”
Section: Introductionmentioning
confidence: 99%
“…They were further limited by reliance on questionnaires for measuring statin use; by lack of information about dose, duration and timing of use; and by grouping all statins regardless of their chemical or pharmacokinetic properties. We recently studied the effects of statins, as a class, on the incidence of several NHL subtypes, including CLL, and estimated an odds ratio (OR) of 0.89 [95% confidence interval (CI), 0.77-1.04) for CLL (18). In this article, we report on the association between CLL and use of several commonly used statins with different chemical structures, pharmacodynamics, and lipid-lowering effects.…”
Section: Introductionmentioning
confidence: 99%
“…In secondary analysis, the association appeared to be restricted to high potency statin and lipophilic statins. 23 Our study could not address the type of statin used. Furthermore, we did not find any associations with other cholesterol lowering drugs.…”
Section: Resultsmentioning
confidence: 93%
“…Interestingly, Ye et al. showed that statin intake may reduce the risk of diffuse large B cell lymphoma ( 13 ). Though statins may play a role in cancer prevention through cholesterol and cholesterol independent pathways ( 14 16 ), statins may induce myositis in rare situations, and inflammation is one of the cancer-causing factors ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%